2009
DOI: 10.1002/ps.1870
|View full text |Cite
|
Sign up to set email alerts
|

What can pest management learn from laboratory animal ethics?

Abstract: There remains a lack of a clear overarching policy framework for decision-making in pest control programmes. In comparison, ethical principles have been extensively developed for scientific procedures, such as those underlying the UK's Animals (Scientific Procedures) Act 1986. This paper assesses the extent to which the principles and methodology underlying the act and secondary guidance could be used to provide principles of rodent management. Useful principles include that any programme has a legitimate purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Since animal welfare is a moral issue [ 51 ], people’s attitudes towards it can vary depending on their culture, area of residence, time, or personal factors [ 52 , 53 ]. Studies in the related literature pointed out that vegetarians based on animal welfare believe that there is a solid emotional bond between humans and animals [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since animal welfare is a moral issue [ 51 ], people’s attitudes towards it can vary depending on their culture, area of residence, time, or personal factors [ 52 , 53 ]. Studies in the related literature pointed out that vegetarians based on animal welfare believe that there is a solid emotional bond between humans and animals [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Van Gerwen et al ( 2020 ) found that almost half of the Dutch pest controllers they interviewed find it difficult to weigh animal interests against those of humans. The growing demand for more rodent control methods that minimise suffering makes it necessary to include animal welfare parameters when dealing with mice and rats as pests (Paparella 2006 ; Beausoleil & Mellor 2015 ), moreover Yeates ( 2010 ) states that pest management can learn from laboratory animal ethics and wildlife management.…”
Section: Introductionmentioning
confidence: 99%
“…In order to facilitate ethical decision-making and include the moral status and welfare of liminal rodents in pest management, various authors have previously indicated animal research ethics as a valuable source. This includes attention for animal welfare (e.g., minimizing suffering), as well as the specific way of justifying actions by means of a decision-making framework [ 6 , 7 , 10 , 11 , 12 ]. Whereas in the research context, animals are subjected to a wide range of different procedures that inflict suffering, requiring ethical assessment, in pest management, the focus lies with the method of killing primarily.…”
Section: Introductionmentioning
confidence: 99%